Owner assessed outcomes following elbow arthroscopy with or without platelet rich plasma for fragmented medial coronoid process - Matos Cruz, Alyssa M.; Mason, David R. (Frontiers in Veterinary Science, 2022)
Objective: Document the outcome of bilateral arthroscopic subtotal coronoidectomy for fragmented medial coronoid process, quantify persistent lameness that required additional treatment (PRP), and document the outcomes of dogs that followed up with PRP injections. Study Design: Retrospective study. Sample Population: Overall, 115 dogs underwent arthroscopy alone and 31 received PRP at least 6 weeks after arthroscopy. Owner response rate was approximately 50% (73 dogs). Methods: Collected data included signalment, unilateral or bilateral clinical signs, intra-articular chondroprotective injection during the procedure, if PRP intra-articular injection was received postoperatively, and if it was received, the time from the initial surgery to administration was recorded. Outcomes were assessed via standardized owner questionnaires using the Liverpool Osteoarthritis in Dogs (LOAD) score, the Canine Brief Pain Inventory (CBPI) score, and overall quality of life (QOL) assessment. Results: Approximately 20% of patients received PRP post-operatively due to persistent lameness following surgery. Similar pain scores were found between the two groups with an average of 11-13 LOAD score, and 13-15 CBPI score, and good quality of life. Older animals at the time of surgery and those that received pain relieving medications after the procedure were more painful and affected their functional outcome. PRP as an adjunctive therapy achieved a perceived good to excellent quality of life in approximately 90% of pets in this population. Conclusion: Arthroscopy and subtotal coronoidectomy followed by PRP, if needed, seemed to decrease pain, and improve lameness in the long term. Clinical Significance: PRP should be considered as adjunctive therapy in dogs with limited response to arthroscopy alone.